Edukasi Hak dan Kewajiban dalam Bermedia Sosial Berdasarkan UU ITE: Upaya dalam Memberikan Batasan Bereskspresi di Media Sosial pada Masyarakat Desa Allang Asaude - Juliaans E. R. Marantika; Fuadiska Salamena; Ronald Darlly Hukubun; Agnes A. Panggabean; Fileo Agus Waileruny (Yayasan Literasi Sains Indonesia, 2025)
In today's digital era, social media has become an integral part of people's daily lives, including the people of Allang Asaude. With easy access to information and communication, social media provides a platform for individuals to express opinions, share information, and interact with others. The socialization of UU ITE (Electronic Information and Transaction Law) is an important step in improving the understanding of the Allang Asaude community regarding the rights and obligations in doing activities in cyberspace, especially in limiting expression. This socialization education aims to educate the community about restrictions on expression under the ITE Law, especially related to freedom of expression, as well as the potential for abuse that can occur in the use of electronic media. The methods used in this socialization include counseling, interactive discussions, and distribution of educational materials tailored to the needs of the audience. The results of the socialization activities showed that community participation was quite active, with increased understanding of the ITE Law and awareness of the importance of communication ethics in the digital space. This activity is expected to build a more aware and responsible society in utilizing information technology, as well as being able to protect themselves from legal risks related to ITE Law.